Inapparent Respiratory Infection of Inbred Swiss Mice with Sulfadiazine-Resistant, Iodine-Negative Chlamydiae - Ata, F. A. (1971)
Three chlamydial strains were isolated from the lungs of three different strains of mice that were inbred for over 30 years. These chlamydial strains were resistant to sulfadiazine and did not induce iodine-positive, glycogen-like material in the inclusions of infected L cells which characterizes them as Chlamydia psittaci.